2016
DOI: 10.1016/j.solener.2016.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Degradation analysis of thin film photovoltaic modules under outdoor long term exposure in Spanish continental climate conditions

Abstract: The present study analyses the degradation of thin film photovoltaic modules corresponding to four technologies: a-Si:H, a-Si:H/μc-Si:H, CIS and CdTe, under 5 years of outdoor long term exposure in Leganés, Spain. The period of outdoor exposure ranges from January 2011 to December 2015. The degradation rate and the stabilization period are analysed by using two different techniques. Moreover, the evolution of the fill factor and performance ratio is assessed. The CdTe module was found to have the highest degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 35 publications
0
19
1
1
Order By: Relevance
“…Only measurements taken at G > 700 W/m 2 were used. Above this irradiance threshold the shape of varying solar spectra closely resembles that of the spectral AM1.5G reference spectrum [11].…”
Section: Effective Peak Power and Degradation Ratementioning
confidence: 68%
“…Only measurements taken at G > 700 W/m 2 were used. Above this irradiance threshold the shape of varying solar spectra closely resembles that of the spectral AM1.5G reference spectrum [11].…”
Section: Effective Peak Power and Degradation Ratementioning
confidence: 68%
“…The reported degradation rate for the Italian weather condition is between 0.15%/year and 0.54%/year over five years of outdoor exposure (Malvoni et al, 2018). Silvestre et al (2016) studied the long term (five years) degradation analysis of silicon-based thin-film PV modules under Spanish continental climate conditions and observed that the CdTe module degrades higher with a value of −4.45%/year. In (Kumar and Malvoni, 2019), a preliminary study quantified the four years degradation of a large-scale c-Si PV system in India to be between 0.30%/year and 0.17%/year.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Regarding long term exposure, the most remarkable effects are permanent damage and power losses. For instance, the long term exposure was studied by Silvestre et al [80] after 5 years in Madrid, Limmanee et al [81], 4 years in Thailand and Chandel et al [82], after 28 years in western India.…”
Section: Outdoor Exposure: Corrosion Delamination and Degradationmentioning
confidence: 99%
“…[79] Algeria Degradation, soiling, delamination. [80] Spain Long term exposure, thin film, modelling. Brazil UAV, I-V curve, thermography.…”
Section: Snow and Ice Depositionmentioning
confidence: 99%